South Africa : Labor Market Dynamics and Inequality - Anand, Rahul (IMF Working Papers; Working Paper ;, 2016)
This paper analyzes the determinants of high unemployment in South Africa by studying labor market dynamics using individual level panel data from the Quarterly Labor Force Survey. While prior work experience and gender are found to be important determinants of the job-finding rate, education attainment and race are important determinants of the job-exit rate. Using stock-flow equations, counterfactual exercises are conducted to quantify the role of these different transition rates on unemployment. The paper also explores the contribution of unemployment towards inequality. Reducing unemployment is found to be important for reducing inequality - estimates suggest that a 10 percentage point reduction in unemployment lowers the Gini coefficient by 3 percent. Achieving a similar reduction solely through transfers would require a 40 percent increase in government transfers.